2005
DOI: 10.1097/01.ccm.0000186767.67870.8c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different resuscitation fluids on tissue blood flow and oxidant injury in experimental rhabdomyolysis

Abstract: HSD prevented oxidant injury and restored tissue blood flow but increased metabolic acidosis that followed autologous muscle extract infusion. SAL/BIC/MAN seems to be more effective than HSD in decreasing oxidant injury. Further research on the effects of the solute overload and metabolic acidosis due to HSD resuscitation on renal function in experimental rhabdomyolysis is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…Effekten av å alkalisere urin er omdiskutert (7,8,26). Behandlingen innebaerer til dels store vaeskemengder intravenøst, noe som medfører økt risiko for komplikasjoner i form av overhydrering.…”
Section: Diskusjonunclassified
“…Effekten av å alkalisere urin er omdiskutert (7,8,26). Behandlingen innebaerer til dels store vaeskemengder intravenøst, noe som medfører økt risiko for komplikasjoner i form av overhydrering.…”
Section: Diskusjonunclassified
“…It has also successfully demonstrated that creatinine kinase > 5000 U/L warrants treatment with a combination of renoprotective strategies, including aggressive hydration, bicarbonate, and mannitol. [2830]…”
Section: Acute Kidney Injury In Polytrauma and Rhabdomyolysismentioning
confidence: 99%
“…Some researchers have reported the addition of bicarbonate to resuscitation fluids to be effective at reducing the incidence of ARF. 45,46 These study designs, however, did not include a control group for resuscitation with only crystalloid solution, which calls into question whether their results were just a function of the aggressive resuscitation rather than the bicarbonate itself. In fact, 2 independent investigators have failed to demonstrate a significant difference between resuscitation with saline versus a bicarbonate solution in the prevention of rhabdomyolysis-induced renal failure.…”
Section: Treatment and Preventionmentioning
confidence: 99%